Dual-wavelength fiber lasers covering the regions of 1.0, 1.5 and 2.0 micron and their applications / Seyed Mohammad Reza Khalifeh Soltanian - Seyed Mohammad Reza, Khalifeh Soltanian (2016)
This report describes the methods and processes of generating tunable dual-wavelength fiber lasers by using three different types of gain media covering three different regions of 1, 1.5 and 2 micron, and an investigation regarding their applications. The homogeneous gain media used in the 1, 1.5, and 2 micron region are ytterbium-doped fiber (YDF), erbium-doped fiber (EDF), and thulium-doped fiber (TDF) respectively. Dual-wavelength fiber laser (DWFL) designs using a selective element, such as photonic crystal fiber (PCF), I discussed in the report in terms of their output power, side mode suppression ratio (SMSR) and tunability. Dual-wavelength fiber laser generation in three different homogeneous medium has been achieved and discussed. Strong mode competition induced by homogeneous broadening represents the main challenge for achieving stable multi-wavelength oscillation at room temperature. By controlling the spatial hole burning, spectral hole burning and polarization states of the modes in the ring laser cavity, new and novel approaches can be proposed to overcome the mode competition issue faced by homogeneous medium for generation of balanced dual-wavelength output. Moreover, modes propagation in PCF is investigated both experimentally and via modeling to attain a deep understanding about the physics behind the generation of DWFL. The modeling results of the field profiles for the fundamental quasi-TM modes are calculated with the vector beam propagation method (BPM). The DWFLs have numerous applications in various fields including fiber sensors and communications. In this study, new designs of DWFLs for various applications are presented and demonstrated. The single longitudinal mode (SLM) properties of the generated DWFL are also investigated and demonstrated. Potential application of DWFL for terahertz rays, the generation of dual-wavelength Q-switched fiber laser, and also the generation of DWFL for microwave generation are presented. All these applications result from the high stability and excellent quality of the fiber laser in terms of output powers and high value of SMSR.